Sonothrombolysis - Christy K. Holland (The Journal of the Acoustical Society of America, 2023)
Cardiovascular disease and stroke are the two leading causes of death worldwide (doi.org/10.1161/CIRCOUTCOMES.118.005375). Sonothrombolysis, ultrasound which accelerates thrombus breakdown in combination with thrombolytic drugs, has been under extensive investigation in the last two decades. An overview of in vitro, preclinical, and clinical sonothrombolysis studies will be provided. In a xenographic porcine cerebral thromboembolism model employing retracted human clots, 220 kHz ultrasound, in conjunction with Definity® increased the probability of early successful reperfusion with rt-PA. Combined treatment with rt-PA, Definity®, and ultrasound invivo increased the rate of reperfusion up to 45 min faster than clots treated with rt-PA or saline alone. Tsivgoulis et al. (doi.org/10.1161/STROKEAHA.120.030960) performed a meta-analysis of sonothrombolysis safety and efficacy data in patients with acute ischemic stroke from 7 randomized-controlled clinical trials. Sonothrombolysis was associated with a 2-fold increase in the odds of complete recanalization compared with intravenous lytic alone. The likelihood of symptomatic intracranial hemorrhage was not significantly different between the 2 groups (7.3% versus 3.7% odds ratio). However, in spite of the higher recanalization rates no difference in 3-month clinical outcomes was uncovered, though this conclusion might have been underpowered statistically. Strategies to improve clinical sonothrombolysis outcomes will be discussed.